Identification of Fel ursi and Cattle and Pig Bile Juices by speciesspecific PCR and PCR-RFLP - Ki-Rok Kwon; Seung-Il Baek; Suk Ho Choi (Korean Pharmacopuncture Institute, 2009)
Objective : This study developed species-specific PCR and PCR-RFLP to detect the adulteration of Fel ursi products with cattle and pig bile juices. Methods : All the primers for PCR and PCR-RFLP in this study were designed based on nucleotide sequences of cytochrome b genes in the mitochondria. Results : The species-specific PCR amplified a DNA fragment of 214, 214, 295, and 167 bp from Felursi product, bear fur, cattle bile juice, and pig bile juice, respectively. The survey using the speciesspecific PCR indicated that some of commercial Fel ursi products were adulterated with cattle and pig bile juices. PCR-RFLP using the restriction endonucleases, HaeIII and HinfI enabled differentiation among Fel ursi product, cattle bile juice, and pig bile juice. Bear furs from two animals showed variations in PCR-RFLP patterns with HaeIII. Discussion : The detection methods of the species-specific PCR and PCR-RFLP could be useful in eliminating adulterated Fel ursi products from the market.